Innovative approaches to project financing management in the context of digitalization: micro- and macro-aspects - Radynskyy, Serghiy; Ratynskiy, Vadym; Krupka, Andrii; Shpylyk, Svitlana; Pohrishchuk, Halyna; Dobizha, Nataliia; Zarichna, Nadiia; Pysmennyi, Vitalii; Piniak, Iryna; Burlitska, Oksana (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is innovative approaches to project finance management in the context of digitalization. The need for the study relates to solving the issue of insufficient adaptation of conventional approaches to project finance management to the conditions of digitalization, which reduces the efficiency of project decision-making and, as a result, the overall level of competitiveness. The study proves that conventional approaches to project finance management are being transformed under the influence of digitalization. A comparative characteristic of traditional and innovative approaches to project finance management is given. The advantages and disadvantages of innovative approaches to project finance management associated with the digitalization of this process have been highlighted. The macro- and micro-aspects of innovative approaches to project finance management in the context of digitalization have been characterized. It was established that at the macro level, innovative approaches to project finance management are influenced by global trends in the evolution of the fintech industry. At the micro level, the implementation of innovative approaches to project finance management is associated with the active use of digital technologies. In order to determine the effectiveness of managing the process under study, a system model of innovative project finance in the context of digitalization was built. A forecast for the development of innovative project finance management over 2026–2030 has been prepared according to the basic, optimistic, and pessimistic scenarios. The practical significance of the results is their use in the development and selection of effective strategies for innovative project finance in the context of digitalization. Quantitative assessment of the research results is meant to improve the conditions for achieving the planned indicators